Upaya Meningkatkan Karakter Disiplin dalam Pencak Silat pada Siswa - Safitri, Henyta Jaya Tria; Muhtar, Tatang; Supriadi, Tedi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to improve the disciplinary character of students in Pencak Silat and find out what the supporting and inhibiting factors are in enhancing the disciplinary character of students in Pencak Silat. This research method uses qualitative research using a case study type, with a Miles & Hubermen model research design with several stages: data collection, data reduction, data display (data presentation), and conclusions (drawing conclusions).The instruments used in this research were observation and interviews. The participants were five students who took part in the pencak silat at Tadjimalela College. This research shows that pencak silat can improve students' disciplined character. And there are also supporting and inhibiting factors. Factors that support efforts to strengthen the disciplined character of students in Pencak silat include getting used to positive thinking, liking to do good, wanting to help other people, the family environment, the school environment, and the community environment. The inhibiting factors are as follows: members are lazy, need help understanding what is being taught, and have bad influence from friends. In conclusion, pencak silat can improve students' disciplined character. Pencak silat contains character values, one of which is the character of discipline. Keywords: Disciplined Character, Pencak Silat